Is MRI helpful in assessing the distance of the tumour from the internal os in patients with cervical cancer below FIGO Stage IB2?. Issue 6 (June 2016) - Bhosale, P.R.; Iyer, R.B.; Ramalingam, P.; Schmeler, K.M.; Wei, W.; Bassett, R.L.; Ramirez, P.T.; Frumovitz, M.
Abstract : Aim: To determine the ability of magnetic resonance imaging (MRI) in detecting tumour-free margins from the internal os (IO). Materials and methods: A database search yielded 79 women with early-stage cervical cancer who underwent radical hysterectomy and preoperative MRI. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of MRI in assessment of ≤5 and >5 mm IO involvement were calculated with histopathological surgical specimen findings considered to be the reference standard. A main and subset analysis was performed. The subset analysis included only those patients who would have been considered for radical trachelectomy. Results: For predicting a distance between the tumour and the IO of ≤5 mm, MRI had a sensitivity of 73%, a specificity of 98.3%, a PPV of 95%, a NPV of 88.1%, and an accuracy of 89.8% for the main analysis, and sensitivity of 81.8%, a specificity of 93.2% a PPV of 69.2% a NPV of 96.5% and an accuracy of 91.4% for the subset analysis. Conclusion: MRI has high specificity, NPV, and accuracy in detecting tumour from the IO, making MRI suitable for treatment planning in patients desiring trachelectomy to preserve fertility. Highlights: Cervical cancer patients who underwent hysterectomy were analyzed on MRI and pathology for involvement of the internal os. Distance of the tumor from the internal-os was measured on MRI and Pathology and findings were tabulated as > and ≤ 5 mm from the internal os. MRI has the ability to identify tumor involvement of the internal os. MRI can help select patients who can undergo trachelectomy safely.